VALIDITY AND RELIABILITY OF THE FOUR SQUARE STEP TEST IN TYPICALLY DEVELOPED CHILDREN - Tuzun, Emine Handan; Eker, Levent; Uzuner, Selma; Sezerel, Buse; Tomac, Hayriye; Mihcioglu, Serpil; Dite, Wayne (Turkey Assoc Physiotherapists, 2020)
Purpose: The purpose of this study was to evaluate the reliability and the validity of the four square step test (FSST), and level of agreement between the FSST and the timed up and go test (TUG) in typically developed children. Methods: Two raters assessed 150 children aged 5 to 10 years in two consecutive days. Concurrent and discriminative validities were determined. To evaluate the intra- and inter-rater reliability, the intra-class correlation coefficient (ICC) was used. The Bland-Altman plot and analysis were performed to evaluate the agreement between the measurements obtained by two raters and by the FSST and TUG. Results: The FSST and TUG scores were strongly correlated (r=0.685, p=0.001). The FSST was able to distinguish between children by age groups (p=0.001). The ICC2.1 and ICC2.2 estimates were 0.86 and 0.81, respectively. For the assessments of two raters, the Bland-Altman plot showed that all values fell within 95% limits of agreement. Bias was calculated as -0.12 +/- 0.50. The 96% of the data points were within the +/- 1.96 SD of the mean difference for the FSST and TUG scores. Bias was calculated as 0.47 +/- 0.80. Conclusion: The FSST is a valid and reliable test to assess the dynamic balance of typically developed children. However, the FSST cannot be substituted for the TUG.
Keywords: Balance; Children; Reliability; Validity